Rh-Catalyzed oxidation and trifluoroethoxylation of N-aryl-pyrrolidin-2-ones: a domino approach for the synthesis of N-aryl-5-(2, 2, 2-trifluoroethoxy)-1, 5-dihydro-2H-pyrrol-2-ones. Issue 6 (8th February 2022) - Luo, Yang; Hu, Mingli; Ge, Jun; Li, Bin; He, Ling
Abstract : A novel rhodium-catalyzed cascade oxidation dehydrogenation/trifluoroethoxylation domino one-pot reaction process for the regioselective synthesis of α, β-unsaturated-γ-trifluoroethoxy-γ-butyrolactams has been successfully developed. Abstract : The synthesis of trifluoroethoxylated dihydropyrrolidones via rhodium-catalyzed oxidation and trifluoroethoxylation of pyrrolidones is presented in this paper. This process realized the trifluoroethoxylation of non-activated sp 3 C–H by a domino approach for the first time, without requiring the preparation of substrates with halogens or guiding groups. The formed α, β-unsaturated-γ-butyrolactams can be further functionalized via the Michael addition reaction or realize the exchange of the trifluoroethoxy group to the hexafluoroisopropoxy group. Such compounds exhibit anti-tumor activity in vitro and can be used as hit compounds for further research. This method provides an efficient domino approach for generating various trifluoroethoxylated dihydropyrrolidones.